THE LANGUAGE MAINTENANCE OF MOTHER TONGUE IN TOURISM AREA, UBUD - Maharani, Sang Ayu Isnu (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
This study entitled "The Language Maintenance of Mother Tongue in Tourism Area, Ubud". The background of this study is departed from having seen the phenomenon of a rapid tourism development in Ubud. The arrival of tourists, both domestics and foreigners, would have an impact on the interaction be-tween tourists and local communities. The interaction is not merely the culture, but also in terms of commu-nication of how the language is being used. The use of language in daily communication is definitely become an interesting aspect to be discussed because Ubud is known as a multicultural region; some people may think that Ubud is a bule village similar to Kuta.The objective of this study is to determine whether mother tongue is still being used in Ubud, Gian-yar or had it replaced by the foreign language. In addition, this research conducted to find out the strategies used by the people of Ubud to maintain the sustainability of mother-tongue language in the region.The method used for this research is a field research. The research conducted by a non-participatory observation; researchers act to make observations and not directly involved in the interaction at the time of the study. Research techniques that used are documentations, records and depth interviews. The results ana-lyzed by approach which was proposed by Fasold (1972). It is also supported by Fishman’s approach; both concern with language maintenance. The interview results are expected to answer strategies used by speakers of the local community in preserving the language. The presentation of the data described in qualitative de-scriptive method.Keywords: Language Maintenance, mother tongue, Tourism area, Ubud